An extrapolation method to determine the effective notch stress in welded joints. Issue 9 (19th April 2015) - Pradana, M. R.; Qian, X.; Swaddiwudhipong, S.; Morel, F.; Nadot, Y.; Buffière, J.‐Y.; Murakami, Y.; Brüne, M.
Abstract This paper presents the development of an extrapolation method to estimate the notch stress in welded steel joints, in line with the effective notch stress concept described in the International Institute of Welding guideline. The proposed approach provides a convenient method to determine the local notch stress at the weld toes without the need to model a finite notch radius as required in engineering guidelines, which creates significant modeling challenges in the numerical procedure, especially for 3‐D joints with a complex topology. An experimental study validates the feasibility of this extrapolation method through strain measurements on cruciform joints. The numerical study then investigates two types of welded connections: (1) cruciform joints with full‐penetration welds and (2) tube‐to‐plate joints. The proposed extrapolation method provides accurate effective notch stress estimations on both joint types, compared with the effective notch stress calculated following the mesh requirement in the existing guidelines.